Komunikasi Organisasi Kantor Desa Tanjung Kecamatan Juwiring Klaten untuk Meningkatkan Kinerja Perangkat Desa dalam Pemberian Pelayanan pada Masyarakat - Wardana, Muhammad Daffa; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
ABSTRACT Service is a right for all people, but it turns out that the right of the community or individuals to obtain services from government officials has not met the expectations of all parties. The purpose of this study was to determine the organizational communication of village officials in providing services to the community. This type of research is descriptive using a qualitative approach. Determination of informants using purposive sampling. Data collection techniques using observation and interviews. Data analysis techniques using interactive analysis. The results showed that the role of organizational communication in the Tanjung Juwiring Klaten Village Office was to create a good service system, where downward communication in the form of instructions, upward communication in the form of reports and horizontal in the form of coordination had gone well, but in the service process it was not yet optimal because there were still shortcomings in the friendliness of village officials in providing services to the community. Keywords: organizational communication, service, performance